Pemberdayaan Kader Dalam Manajemen KIPI Pada Vaksinasi Covid-19 Di Wilayah Kerja Puskesmas Bandarharjo - Rani Tiyas Budiyanti; Nurhasmadiar Nandini; Sutopo Patria Jati; Septo Pawelas Arso; Eka Yunila Fatmasari (Indonesian Journal Publisher, 2022)
Indonesia targeting that at least 70% of the population vaccinated and formed the herd immunity. However, there are several challenges in reaching that target, such as the anti-vaccine movements, disinformation or hoaxes, fear of the Adverse Event Following Immunization (AEFI), and fear of needles. Based on the preliminary study, the area of Bandarharjo Public Health Centre was in the lowest 3rd place related to the COVID-19 vaccination coverage in Semarang. This was due to lack of education to the community regarding the vaccination, the high resistance to vaccination due to concerns about AEFI, and so on. Health cadres are one of the main actors in the supporting the health programs in PHC, therefore the role of health cadres need to be optimized in education and management of AEFI related to COVID-19 vaccination. This community service program was carried out offline in 30 health cadres in the working area of Bandarharjo PHC. The activity began with a pre-test, continued with the presentation of the topic, discussion session, and ends with post-test. The results of the pre-test and post-test showed that there was an increase in the knowledge of cadres between before the presentation and after the presentation session. Health cadres also received booklets containing general information about COVID-18 vaccination and also related to AEFI. Booklets given to cadres not only to increase their knowledge but also can be used to educate the community. Hopefully, with the increase in knowledge and understanding of cadres, the community will be easily get the right information. The health cadres commitment to educate the community regarding COVID-19 vaccination also hoped to increase the community knowledge related to the vaccination and also the willingness of community to receive the COVID-19 vaccination, especially in the working area of Bandarharjo PHC, Semarang City, Central Java Province.